Lower-limb rehabilitation robot design - Bouhabba, El Mehdi; Shafie, Amir Akramin; Khan, Md. Raisuddin; Ariffin, Kamarul Ariffin (IOP Publishing, 2013)
It is a general assumption that robotics will play an important role in therapy activities within rehabilitation treatment. In the last decade, the interest in the field has grown exponentially mainly due to the initial success of the early systems and the growing demand caused by increasing numbers of stroke patients and their associate rehabilitation costs. As a result, robot therapy systems have been developed worldwide for training of both the upper and lower extremities. This paper investigates and proposes a lower-limb rehabilitation robot that is used to help patients with lower-limb paralysis to improve and resume physical functions. The proposed rehabilitation robot features three rotary joints forced by electric motors providing linear motions. The paper covers mechanism design and optimization, kinematics analysis, trajectory planning, wearable sensors, and the control system design. The design and control system demonstrate that the proposed rehabilitation robot is safe and reliable with the effective design and better kinematic performance.